Sistematización de los defectos en la forma del acto administrativo: revisión de literatura integrativa - Rojas Barrientos, Sergio Rodrigo (2023)
The purpose of this research is to identify all the defects of the administrative act associated with the element of validity form. To meet this objective, a systematic, exhaustive and replicable literature review was carried out, whose purpose was to select all reliable academic documents that address the form as an element of validity. During the reading of the selected documents, all the relevant doctrinal positions that alluded to any of the following topics were collected and collated: nature of the form as an element of validity of the administrative act, definition of form as an element of validity of the administrative act, classification of the external manifestations of the administrative act and defects under the domain of element of validity form. All the positions identified were integrated in an internally coherent scheme that is capable of discriminating formal defects from other types of defects. As a result of the integrative review of the selected documents, a comprehensive catalog of defects associated with the element of validity form was developed, which allows to objectively determine whether a defect is formal or of another nature.